Diversity and Discrimination in Research Organizations - Striebing, Clemens; Müller, Jörg (Researcher in gender equality); Schraudner, Martina (Emerald Publishing Limited, 2023)
The ebook edition of this title is Open Access and freely available to read online. The era of team science has long since dawned. However, in order for the individual members of a team to work well, research organizations need to provide a productive and naturally non-discriminatory working environment. Bringing together and integrating researchers and their diverse backgrounds in effective teams does not happen on its own. To harness the positive effects of diversity, it must be understood and managed proactively. The edited collection Diversity and Discrimination in Research Organizations provides researchers with empirical studies on the question of whether and to what extent the social identity of the academic workforce affects their individual integration in research organizations. Practitioners receive guidance and suggestions on possible starting points and requirements for programmes to improve equal opportunities and work climate in their research organizations. The articles can be roughly divided into two categories according to the guiding questions of this edited collection: macro studies surveying the extent of discrimination and harassment in research organizations and micro studies exploring the influence of the specific cultural contextual conditions of the academic workplace on experiences of discrimination and harassment related to the diversity of the workforce.